Product Warranty Period: A Markovian Approach to Estimation and Analysis of Repair and Replacement Costs. - Balachandran, K. R.; Maschmeyer, Richard A.; Livingstone, J. Leslie (The Accounting Review, 1981)
ABSTRACT: This article describes the repair-replacement process of a product under warranty as a stochastic process and develops a model to estimate the costs due to warranty. The product is assumed to be made up of several components for which failure rates are available. Markovian states are defined dependent on the number of failures of each component. A replacement policy is superimposed, and an approach to obtaining the transition probabilities is illustrated when the failures are solely due to chance. The use of the model to estimate the warranty costs during an accounting period, when there are warranties outstanding for the products sold during prior periods in addition to the products sold during the current period, is discussed.